Nijmegen breakage syndrome: The importance of follow-up - Leite,Sara (2023)
Abstract Nijmegen breakage syndrome (NBS) is a rare genetic disorder caused by mutations in the NBN gene, which is inherited in an autosomal recessive pattern. The condition results in inadequate DNA repair and is characterized by immunodeficiency with recurrent sinopulmonary infections, increased radiosensitivity, and predisposition to malignancy, particularly of lymphoid origin. The main clinical feature is progressive and severe microcephaly, which affects the facial phenotype, characterized by prominent midface, sloping forehead, and retrognathia. Mild to moderate intellectual impairment is often present and female patients usually develop primary ovarian failure. The diagnosis requires a high index of suspicion and is confirmed by molecular genetic testing. Herein are presented two cases of Nijmegen breakage syndrome followed in a tertiary center.